Stromal interaction molecule 1 (STIM1) knock down attenuates invasion and proliferation and enhances the expression of thyroid-specific proteins in human follicular thyroid cancer cells - Asghar Muhammad Yasir; Lassila Taru; Paatero Ilkka; Nguyen Van Dien; Kronqvist Pauliina; Zhang Jixi; Slita Anna; Löf Christoffer; Zhou You; Rosenholm Jessica; Törnquist Kid (SPRINGER BASEL AG, 2022)
Stromal interaction molecule 1 (STIM1) and the ORAI1 calcium channel mediate store-operated calcium entry (SOCE) and regulate a multitude of cellular functions. The identity and function of these proteins in thyroid cancer remain elusive. We show that STIM1 and ORAI1 expression is elevated in thyroid cancer cell lines, compared to primary thyroid cells. Knock-down of STIM1 or ORAI1 attenuated SOCE, reduced invasion, and the expression of promigratory sphingosine 1-phosphate and vascular endothelial growth factor-2 receptors in thyroid cancer ML-1 cells. Cell proliferation was attenuated in these knock-down cells due to increased G1 phase of the cell cycle and enhanced expression of cyclin-dependent kinase inhibitory proteins p21 and p27. STIM1 protein was upregulated in thyroid cancer tissue, compared to normal tissue. Downregulation of STIM1 restored expression of thyroid stimulating hormone receptor, thyroid specific proteins and increased iodine uptake. STIM1 knockdown ML-1 cells were more susceptible to chemotherapeutic drugs, and significantly reduced tumor growth in Zebrafish. Furthermore, STIM1-siRNA-loaded mesoporous polydopamine nanoparticles attenuated invasion and proliferation of ML-1 cells. Taken together, our data suggest that STIM1 is a potential diagnostic and therapeutic target for treatment of thyroid cancer.